Liquid phase exfoliation and dispersion of two dimensional materials - Smith, Rónán (Trinity College (Dublin, Ireland). School of Physics, 2014)
Over the last few years, it has become clear that due to their high surface area and novel properties, two dimensional materials will be extremely useful both for fundamental studies and for a range of applications. Previous work has shown that graphene can be produced in large quantities by exfoliation of graphite in certain solvents or surfactants. Of these methods, surfactant dispersion is perhaps the most promising because the use of toxic solvents is avoided. Although previous work has shown that such methods give reasonably large quantities of good-quality graphene, there is still much scope for improvement as well as further investigation.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin